Profile of the Psychomotrician in Brazil: the birth for initial training (Research, Society and Development, 2022)
While there is still no degree in Psychomotricity in Brazil, the interest in identifying the profile of the professional who works in this area will contribute to the rise of the profession, as well as the scientific support necessary for the theoretical contribution of the area. In addition, knowing how the current psychomotorist acted during the period of social isolation reinforces the importance of this profession. The influence of initial training on professional performance, together with personal experiences, predict beliefs. Thus, through an online questionnaire, the predominance of women's participation in Psychomotricity was identified. The professions that seek to qualify in a lato sensu postgraduate course come from Pedagogy, Physical Education and Psychology as predominant. Its main field of action is the clinic and the same was continued during the pandemic and expanded to home care, in many cases, due to the need for care. Finally, there is no defined identity of the psychomotor driver in Brazil. It is also important to emphasize that during the pandemic, the calls continued in person in the clinical scope, within a remote perspective, in most of the follow-ups.